The Politics of Research Production, Promotion, and Utilization in Educational Policy. (March 2014) - Lubienski, Christopher; Scott, Janelle; DeBray, Elizabeth
Researchers have noted with concern the often weak link between research evidence and policymaking, particularly in some areas such as education. In this introductory essay—dedicated to the late Carol Weiss—we consider this issue first by reflecting on how changing historical conditions can shape institutional demands on and for research production, promotion, and use. This leads to the questions: How can institutions use evidence on different policy options? How do policymakers and other information consumers sort through competing claims? Are new processes and institutions emerging to shape research use? In view of the current calls from public policymakers in the government and private policymakers in philanthropies for rigorous research on the effectiveness of policy interventions, we compare the relative role of research use in education policy to other issues, such as climate science, and highlight the growing role of intermediate actors as they shape research use. And we consider some common characteristics of these policy issues that may contribute to misuse or disuse, as well as to greater consideration of research. We offer an overview of the understanding of research use in education and point to the need to explore new theoretical frameworks and methodologies. The essay ends with an overview of the papers in the issue.